"Harsh play": The dark tetrad of personality, trolling and cyberbullying among the university students in South Africa - Mashaba, Lele, Hellen (My University, 2020)
Incidents associated with internet trolling and cyberbullying are a problem among adolescents. A quantitative research method was applied in this study to explore if attitudes towards cyberbullying can mediate the association between the Dark Tetrads of personality and internet trolling among undergraduate University students in South Africa.. A convenience sample (N = 249) of undergraduates was recruited, and data were collected using a structured, composite questionnaire, within a cross-sectional research design. The findings indicated that there was a small but statistically significant indirect effect, b = 0.4, BCa CI [0.015, 0.071]. A more nuanced analysis showed that only the mediation models involving psychopathy and everyday sadism as independent variables were statistically significant (p < .05). From the results, it can be concluded that internet trolling does mediate the relationship between the Dark Tetrads of personality and attitudes towards cyberbullying. However, the Dark Tetrad personality dimensions of Machiavellianism and narcissism are not significantly involved in the relationship.
Thesis(M. A. (Research Psychology)) -- University of Limpopo, 2020
Keywords: Dark tetrads of personality; Cyberbullying; Attitude torwards cyberbullying; Internet trolling; Threatened egotism theory; Cyberbullying; Character; Online trolling; Students -- Psychology; Personality